Evaluación de cepas de Trichoderma spp como bioestimulante en el crecimiento y rendimiento del cultivo de pimiento - Sabando Zambrano, Gabriel Alexander (2022)
Sometimes, cultivated plants have limited vegetative and productive development because they are exposed to nutrient deficiencies in soils with low natural fertility or to poor nutrient solubility, as occurs with phosphorus; given this, in the present work it was proposed to evaluate strains of Trichoderma spp as biostimulants in the growth and yield of the H. Salvador pepper crop. The first phase of the study was carried out under laboratory conditions, 14 Trichoderma strains were used to determine tricalcium phosphate solubilization, siderophore detection and stimulating effect on pepper seed germination and root length. For the field phase, two strains of Trichoderma were selected; an experiment was carried out with each one, using a completely randomized design and four replications, where the concentration of the microorganism (102, 103, 104) and two witnesses were evaluated on: root length, plant height, fresh and dry weight of the plant, and number of fruits per plant. In vitro, the promising strains were EM-12 and EM-134, which were identified as T. longibrachiaum and Trichoderma sp. In the vegetative variables, a similar response was found between the two strains evaluated and the positive control (soluble phosphate); however, the number of fruits was higher when applying Trichoderma sp (4.5) than T. longibrachiaum (3.5). According to the statistical categories, the highest concentration of the inoculum has positive effects on the plant. It is concluded that the selected strains acted as plant growth promoters.